Desain dan Pengembangan Pembelajaran Bahasa Arab Berbasis Pendidikan Karakter di Madrasah - Akla Akla (Tarbawiyah Jurnal Ilmiah Pendidikan, 2016)
The damage of the young generation’s character is already grounded. This damage of character is indicated by a large circulation of video porn among students, rampant free sex among adolescents, drug trafficking and fighting among the students. Consequently, this becomes aresponsibility of every teacher including Arabic language teacher to reorganize and align irrelevant behaviors by internalizing the values of characters in each subject. This article discusses how to internalize those values. One concrete step is to design and develop a character-based Arabic language learning. In designing and developing acharacter-based Arabic learning, ADDIE model design can be used. This model is designed with stages consisting of Analysis, Design, Development, Implementation, and Evaluation. Analysis is an activity to find out the needs of learners and madrasah institutions related to what kind of skills and character is needed. Design is identifying sub capabilities required for students to be able to master expected competencies. Development means the development of adapted character-based Arabic language learning to be used in delivering the contents of the set goals. Implementation is the application of a design developed to determine the effectiveness of Arabic language learning.